A Comprehensive Review on the Development of Natural and Biomimetic Bouligand Structure Materials - Li, Jiahui; Hu, Jiahe; Zhang, Jinglong (International Journal of Materials Science and Technology Studies, 2026)
The Bouligand structure, also known as a helicoidal fibrous structure, appears extensively in natural biological tissues with excellent mechanical properties, such as the dactyl clubs of mantis shrimp, the exoskeletons of lobsters, and the scales of fish; because this highly unique layer-by-layer architecture is formed by stacking single-direction fibrous sheets in a spiral manner at specific angles, it can equip biological tissues with exceptional fracture resistance, anti-impact capabilities, and damage tolerance; if the relationship between this structure and its performance can be thoroughly understood, and this mechanism can then be applied to artificially manufactured systems, it would be of immense value for the development of new, high-performance composite materials; this article primarily lists classic examples of Bouligand structures in natural environments, carefully analyzes the internal principles that enable it to increase material toughness, which include crack deflection, crack twisting, and the bridging effect between fibers, and summarizes the main methods used in recent years to artificially biomimic and manufacture this structural material, such as 3D printing, material self-assembly, and assembly through shear forces, while also forecasting the roles this material could play in fields like aerospace, national defense, and medical health in the future.